Annual Plan 2004-2005 West Bengal - Planning Commission (Planning Commission, 2004)
There has been remarkable achievements in the production of foodgrains in the State of West Bengal in recent years. It has been achieved top most (1st) position in the country in total production of rice, jute and vegetables. This has been the result of progressive and systematic planning and implementation of various crop development programmes/schemes (State Plan, Central Sector and Centrally Sponsored Schemes) launched by the State Govt., the dedication of our people engaged in agriculture, involvement of "Panchayati Raj System" and application of modern crop production technology in the field. the average production of foodgrains during Ninth Plan period was 147.78 lakh tonnes.
Development and Planning Department Government of West Bengal